Identification of Key Endometrial MicroRNAs and Their Target Genes Associated With Pathogenesis of Recurrent Implantation Failure by Integrated Bioinformatics Analysis - Shang, Jin; Cheng, Yan-Fei; Li, Min; Wang, Hui; Zhang, Jin-Ning; Guo, Xin-Meng; Cao, Dan-dan; Yao, Yuan-Qing (Frontiers in Genetics, 2022)
Purpose: Recurrent implantation failure (RIF) is an enormous challenge for In Vitro Fertilization (IVF) clinicians. Understanding of the molecular mechanisms of RIF helps to predict prognosis and develop new therapeutic strategies. The study is designed to identify diagnosis biomarkers for RIF, as well as the potential mechanisms underlying RIF by utilizing public databases together with experimental validation. Methods: Two microarray datasets of RIF patients and healthy controls endometrium were downloaded from the Gene Expression Omnibus (GEO) database. Firstly, differentially expressed microRNAs(miRNAs) (DEMs) were identified and their target genes were predicted. Then we identified differentially expressed genes (DEGs) and selected hub genes through Protein-protein interaction (PPI) analyses. Functional enrichment analyses of DEGs and DEMs were conducted. Furthermore, the key DEMs which targeted those hub genes were selected to obtain key miRNA-target genes network. The key genes in miRNA-target genes network were validation by a single cell RNA-sequencing dataset of endometrium from GEO. Finally, we selected two miRNA-target genes pairs to further experimental validation used dual-luciferase assay and quantitative PCR (qPCR). Results: We identified 49 DEMs between RIF patients and fertile group and found 136,678 target genes. Then 325 DEGs were totally used to construct PPI network, and 33 hub genes were selected. 25 DEMs targeted 16 key DEGs were obtained to establish key miRNA-target genes network, and 16 key DEGs were validated by single cell RNA-sequencing dataset. Finally, the target relationship of hsa-miR-199a-5p-PDPN and hsa-miR-4306-PAX2 were verified by dual-luciferase assay, and there were significant differences in the expression of those genes between RIF and fertile group by PCR (P<0.05). Conclusion: We constructed miRNA-target gene regulatory networks associated with RIF which provide new insights regarding the underlying pathogenesis of RIF. hsa-miR-199a-5p-PDPN, hsa-miR-4306-PAX2 could be further explored as potential biomarkers for RIF, and their detection in endometrium could be applied in clinics to estimate the probability of successful embryo transfer.